Pengaruh Team Games Tournament dan Numbered Heads Together terhadap Hasil Belajar Siswa - Daga, Agustinus Tanggu; Paila, Agustina Mersiana; Lende, Petrus (Paedagogie, 2026)
This study aims to compare the effects of the Team Games Tournament (TGT) and Numbered Heads Together (NHT) models on elementary students' mathematics learning outcomes. Conducted with fifth-grade students at SDK Bali Loura using a quasi-experimental design, data were collected via a validated 10-item multiple-choice test, as verified by mathematics education experts. Data analysis encompassed descriptive statistics (pretest and posttest means), prerequisite tests (normality and homogeneity), and hypothesis testing (paired samples t-test and independent t-test). Results revealed: (1) TGT group pretest and posttest means of 40.7 and 85, respectively, versus NHT's 38.6 and 71.4; (2) Normality tests yielded significance values of 0.115 (TGT) and 0.251 (NHT), both >0.05, indicating normal distribution; homogeneity significance was 0.889 (>0.05), confirming homogeneity; (3) Paired samples t-tests for both groups showed significance of 0.000 (<0.05), signifying significant pretest-posttest differences; the independent t-test yielded 0.001 (<0.05), indicating significant mean differences between TGT and NHT groups.